Optical Coherence Tomography Imaging in Acute Coronary Syndromes - Takashi Kubo; Yasushi Ino; Takashi Tanimoto; Hironori Kitabata; Atsushi Tanaka; Takashi Akasaka (Cardiology Research and Practice, 2011)
Optical coherence tomography (OCT) is a high-resolution imaging technique that offers microscopic visualization of coronary plaques. The clear and detailed images of OCT generate an intense interest in adopting this technique for both clinical and research purposes. Recent studies have shown that OCT is useful for the assessment of coronary atherosclerotic plaques, in particular the assessment of plaque rupture, erosion, and intracoronary thrombus in patients with acute coronary syndrome. In addition, OCT may enable identifying thin-cap fibroatheroma, the proliferation of vasa vasorum, and the distribution of macrophages surrounding vulnerable plaques. With its ability to view atherosclerotic lesions in vivo with such high resolution, OCT provides cardiologists with the tool they need to better understand the thrombosis-prone vulnerable plaques and acute coronary syndromes. This paper reviews the possibility of OCT for identification of vulnerable plaques in vivo.